On the origin of the below band-gap absorption bands in n-type (N) 4H-and 6H-SiC - Weingärtner, Roland; Wellmann, Peter; Winnacker, Albrecht (Materials Science Forum, 2004)
The dopant concentration dependence of the below band-gap absorption bands at room temperature in n-type (N) 4H- and 6H-SiC are investigated. The occupation of the nitrogen donors are determined from temperature dependent Hall effect measurements. In combination with the strength of the absorption bands the cross sections of these transitions are obtained. It is shown that the below band-gap absorption bands may be attributed to the inequivalent lattice sites of the nitrogen donor, i.e. the transition is defect-like with different initial states of the nitrogen donors and a common final state in the conduction ban
Keywords: Absorption Band; Cross Section; Hall-Effect; Inequivalent Lattice Sites; Nitrogen Donor